2021
DOI: 10.3390/cancers13246209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Breast Cancer Stem Cells in Chemoresistance and Metastasis in Triple-Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) remains an aggressive disease due to the lack of targeted therapies and relatively low rate of response to chemotherapy, which is currently the main treatment modality for TNBC. Breast cancer stem cells (BCSCs) are a small subpopulation of breast tumors and recognized as drivers of tumorigenesis. TNBC tumors are characterized as being enriched for BCSCs. Studies have demonstrated the role of BCSCs as the source of metastatic disease and chemoresistance in TNBC. Multiple tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 120 publications
0
24
0
Order By: Relevance
“…Recent articles have reviewed the importance of CSCs in TNBC progression and therapeutic resistance [ 18 , 19 , 20 , 21 , 22 , 23 ]. TNBCs are enriched with CD44+/CD24−/ALDH1+ CSCs that contribute to metastases, chemoresistance and poor clinical outcomes [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent articles have reviewed the importance of CSCs in TNBC progression and therapeutic resistance [ 18 , 19 , 20 , 21 , 22 , 23 ]. TNBCs are enriched with CD44+/CD24−/ALDH1+ CSCs that contribute to metastases, chemoresistance and poor clinical outcomes [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Sonic Hedgehog (SHH) has also been identified as a pathway that contributes to the TNBC CSC state [ 33 , 34 , 35 ]. Agents that target WNT, NF-κB, NOTCH and SHH signaling are under development to eliminate CSCs in TNBCs, as well as other cancers [ 20 , 21 ]. Along these lines, small molecule inhibitors of WNT/β-catenin/TCF signaling are being developed based on their inhibition of TNBC CSCs in cell line and tumor models [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cancer stroma cells use Warburg metabolism, whereas cancer stem cells’ metabolism is driven by mitochondrial oxidation [ 33 ]. In breast cancer, there are two types of cancer stem cells: CD44+/CD24 mesenchymal-like cancer stem cells and aldehyde dehydrogenase 1 family, member A1 (ALDH1) positive epithelial-like cancer stem cells [ 34 ]. Inhibiting mitochondrial oxidation can increase the proportion of cancer stroma to stem cells, allowing conventional chemotherapy to be more effective against stromal cells.…”
Section: Immunometabolismmentioning
confidence: 99%
“…Moreover, we further evaluated the effects of Dicer on the cell migratory/ invasive abilities and found that Dicer silencing enhanced both cell migration and invasion (Figure 3B). In addition, cancer stemness is a primary driver of cancer recurrence and metastasis [24][25][26]. Therefore, we surmised that Dicer participates in regulating the CSCs properties of breast cancer cells.…”
Section: Inhibition Of Dicer Expression Promotes the Migration Invasi...mentioning
confidence: 99%